2016
DOI: 10.1016/j.jotr.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Treatment Modality of Hand Enchondroma in a Local Hospital: From Autograft to Artificial Bone Substitutes

Abstract: Background/Purpose: Curettage followed by the application of iliac crest autograft was the traditional treatment of hand enchondroma in Princess Margaret Hospital, Hong Kong. Methods: We reviewed the results of 13 patients with hand enchondroma who were operated on in the past 15 years (1999e2013). Eight patients (1999e2009) received iliac crest autograft after curettage, whereas the other five patients (2009e2013) received artificial bone substitutes. Results: Both groups of patients had good functional outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In our study, graft consolidation was detected in all patients during control radiography in the sixth week. In the literature, it was reported that incorporation developed within a similar period among patients with autografts [24][25]. Our study demonstrated that usually good or excellent functional and radiologic results were obtained from curettage and autologous bone grafting with a histological diagnosis of enchondroma.…”
Section: Discussionsupporting
confidence: 65%
“…In our study, graft consolidation was detected in all patients during control radiography in the sixth week. In the literature, it was reported that incorporation developed within a similar period among patients with autografts [24][25]. Our study demonstrated that usually good or excellent functional and radiologic results were obtained from curettage and autologous bone grafting with a histological diagnosis of enchondroma.…”
Section: Discussionsupporting
confidence: 65%
“…DBX was used as a graft in the treatment of enchondromas of the hand. Kwon and Wong, 34 and Dietz, Kachar and Nagle, 33 reported small case series of five and two patients, respectively. No recurrence or pathological fractures were reported.…”
Section: Resultsmentioning
confidence: 99%